DPHB, a diarylheptane from Alpinia officinarum Hance, ameliorates insulin resistance: A network pharmacology and in vitro study - Li, Xiangyi; Wen, Huan; Zhang, Yuxin; Liu, Aixia; Zhang, Xuguang; Fu, Minghai; Pan, Yipeng; Xu, Jian; Zhang, Junqing (Frontiers in Pharmacology, 2022)
(4E)-7-(4-Hydroxy-3-methoxyphenyl)-1-phenylhept-4-en-3-one (DPHB) derived from Alpinia officinarum Hance has been reported to exert anti-inflammatory and anti-insulin resistance (IR) effects. We explored the molecular mechanism of DPHB ameliorating IR through network pharmacological prediction and in vitro analysis. The PI3K/AKT and TNF signaling pathways are the core pathways for DPHB to exert anti-IR, and the key proteins of this pathway were confirmed by molecular docking. In the IR-3T3-L1 adipocytes model, DPHB significantly promoted glucose uptake and the glucose transporter type 4 (GLUT4) translocation. In addition, DPHB significantly improved lipid accumulation, triglyceride content, and the mRNA expression of key adipokines (such as peroxisome proliferators-activated receptors-gama (PPARγ), CCAAT enhancer binding protein alpha (C/EBPα), sterol regulatory element-binding protein-1 (SREBP-1)). DPHB inhibited the protein expression of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and phosphorylated nuclear factor-κB (NF-kB), as well as promoted the expression of hosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT), phosphorylated PI3K, and phosphorylated AKT. More interestingly, validation of the PI3K inhibitor LY294002 revealed that these changes were dependent on the activation of PI3K. Our cumulative findings thereby validate the potential of DPHB to alleviate and treat IR and the related diseases by regulating the PI3K/AKT and TNF-α signaling pathways.